2022
DOI: 10.1108/jima-08-2021-0266
|View full text |Cite
|
Sign up to set email alerts
|

Measuring halal logistics implementation

Abstract: Purpose This study aims to identify the suitable indicators and their scale for measuring the level of logistic halal implementation and then develops the measurement system based on those indicators and scales. Moreover, this research also applies the measurement system in food, beverage, and ingredient companies. Design/methodology/approach This study collected data through web-based closed questionnaires and short telephone interviews. This study succeeded in obtaining seven valid data sets from filling o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
(91 reference statements)
0
6
0
Order By: Relevance
“…Domestic apples are preferable because of attributes of quality (in order: juiciness, appearance, freshness and aroma), cultivars (in order: Rome Beauty and Manalagi variety) and purchasing place (in order: fruit stalls and supermarket) (Relawati et al, 2017). The other study in Indonesia found that consumers prefer domestic apples because of the -Teinaz, 2020a-Teinaz, , 2020bAlzeer et al, 2018;Soon et al, 2017;Susanty et al, 2022;Tan et al, 2017) JIMA 15,5 factors of performance (size, colour, packaging, label, texture, ease of obtaining and taste), appearance (freshness and cleanliness) and green product (organic and benefit) (Isaskar and Perwitasari, 2021). In contrast, imported apples are preferred because of attributes of quality (in order: appearance, texture, aroma and juiciness), cultivars (in order: Fuji and Washington variety) and purchasing place (in order: fruit stalls and supermarkets) (Relawati et al, 2017).…”
Section: Food Mile Problems Under Halal Supply Chainmentioning
confidence: 99%
“…Domestic apples are preferable because of attributes of quality (in order: juiciness, appearance, freshness and aroma), cultivars (in order: Rome Beauty and Manalagi variety) and purchasing place (in order: fruit stalls and supermarket) (Relawati et al, 2017). The other study in Indonesia found that consumers prefer domestic apples because of the -Teinaz, 2020a-Teinaz, , 2020bAlzeer et al, 2018;Soon et al, 2017;Susanty et al, 2022;Tan et al, 2017) JIMA 15,5 factors of performance (size, colour, packaging, label, texture, ease of obtaining and taste), appearance (freshness and cleanliness) and green product (organic and benefit) (Isaskar and Perwitasari, 2021). In contrast, imported apples are preferred because of attributes of quality (in order: appearance, texture, aroma and juiciness), cultivars (in order: Fuji and Washington variety) and purchasing place (in order: fruit stalls and supermarkets) (Relawati et al, 2017).…”
Section: Food Mile Problems Under Halal Supply Chainmentioning
confidence: 99%
“…Hassan et al (2016) argue that the efficiency and success of HSCM may be improved by integrating halal-related elements including certifying authorities, vendors, and operations and logistics. As such, recent literature on HSCM has given attention to the four main activities, namely halal procurement (Tieman et al, 2020;Shari et al, 2021), halal manufacturing (Mohamed et al, 2016;Samsudin & Dani, 2022), halal distribution and halal logistics (Zailani et al, 2017;Susanty et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thirdly, MSE owners should enforce stringent segregation measures [91,92]. Rigorous separation between halal and nonhalal products is essential to comply with halal standards.…”
Section: Solution For Issues Warehousing and Distributionmentioning
confidence: 99%